Pengaruh Tingkat Pendidikan, Jumlah Anggota Keluarga, Jam Kerja, dan Status Perkawinan terhadap Tingkat Pendapatan Masyarakat Kelurahan Tengah Kecamatan Pelayangan Kota Jambi - Inayah, Dina; Bukit, Pantun; Susilawati, Susilawati; Adisetiawan, R. (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the influence of education level, number of family members, working hours, and marital status on income levels in the Tengah Village, Pelayangan District, Jambi City. This study was a quantitative descriptive study with a sample size of 162 families. Multiple linear regression was used as the analytical tool. The results revealed a simultaneous positive and significant influence between education level, number of family members, working hours, and marital status on income levels. However, only the number of family members had a partial effect on income levels in the Tengah Village, Pelayangan District, Jambi City.